2016
DOI: 10.1093/occmed/kqw169
|View full text |Cite
|
Sign up to set email alerts
|

Do workplace interventions reduce disability rates?

Abstract: BackgroundIncreasing life expectancy and decreasing fertility have led to a shift in the workforce age structure towards older age groups. Deteriorating health and reduced work capacity are among the challenges to retaining older workers in the labour force.AimsTo examine whether workplace interventions to facilitate work among employees with health problems or reduced work capacity affect disability rates among employees aged 50 years and older.MethodsData from a survey of Norwegian companies (n = 713) were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
3
17
0
1
Order By: Relevance
“…Beyond these two studies, there is little scienti c knowledge on the impact of the IA Agreement on sickness absence that also takes into account the possible differential impacts by industry. Other scienti cally based evaluations of the IA Agreement have been carried out, largely reporting a positive impact, however, they have evaluated other outcomes, such as disability bene ts (10) and return to work after rehabilitation (9), and are therefore not comparable to our study.…”
Section: Methodological Considerationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Beyond these two studies, there is little scienti c knowledge on the impact of the IA Agreement on sickness absence that also takes into account the possible differential impacts by industry. Other scienti cally based evaluations of the IA Agreement have been carried out, largely reporting a positive impact, however, they have evaluated other outcomes, such as disability bene ts (10) and return to work after rehabilitation (9), and are therefore not comparable to our study.…”
Section: Methodological Considerationsmentioning
confidence: 81%
“…Two studies showed no impact on SA (7,8), while more recent studies, using causal inference methods, found positive impacts with a higher probability of returning to work (9) and a lower likelihood of receiving a full disability pension (10). These studies are, however, done on selected samples, such as participants on work rehabilitation (9) and older employees aged 50-61 (10), highlighting the need for studies on other samples/cohorts.…”
mentioning
confidence: 98%
“…The key role of Finnish OHS is to provide healthcare services to organisations' employees, during which they can identify patients at risk of work-related diseases, and identify injuries and illnesses that threaten an employee's ability to work [13]. They are in a key position in the country to implement workplace interventions that can help prevent work-related diseases and decrease rates of work disability [14]. However, to date, little research has been conducted on the effectiveness of OHS in preventing work disability.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational rehabilitation is a growing field of research and practice that has contributed to significant developments towards understanding the return-to-work (RTW) process and facilitating RTW outcomes. However, studies of RTW practices indicate variable [1] or minor changes to overall work disability rates [2,3]. This has been, at least in part, attributed to a lack of a comprehensive theoretical framework addressing work disability and RTW.…”
Section: Introductionmentioning
confidence: 99%